More than half his mind: John Donne's Pseudo-Martyr and the matter of sovereignty. Issue 4 (3rd July 2020) - Read, David
ABSTRACT: The difficulty of reading Pseudo-Martyr, Donne's tract in defence of English Catholics taking the Oath of Allegiance, has allowed certain generalizations about it to persist without receiving much scrutiny, notably John Carey's remark that Donne wrote it with "only half his mind, " mainly to "curry favour" with James I. This essay joins the relatively small number of readings that respect the work as a serious project in political theory. I argue that Donne is working out a concept of sovereignty based on his ideas about the law of nature and "right reason." In brief, humans have a natural desire to be ruled and organize their societies around this desire, which originates in the order of God's creation but manifests itself in secular ruler-ship. Donne's use of the Venetian Republic as an example points to his idea that this ruler-ship need not take the form of absolute monarchy.